Exploring the mental health impact of COVID-19 on parents of young children: anxiety, depression, and contributing factors - Elisa Rodríguez-Toscano; Daniel Schleicher; Angelika Ecker; Stephanie Kandsperger; Romuald Brunner; Irina Jarvers (BMC Public Health)
Abstract Background The COVID-19 pandemic led to a global shutdown, with most countries implementing widespread lockdowns. While such measures were essential in curbing the spread of COVID-19, their impact on the mental health of parents with preschool-aged children is not yet sufficiently understood. This study aimed to assess anxiety and depression symptoms in parents during and after the COVID-19 lockdowns, and to examine how demographic and pandemic-related factors influenced these outcomes. Method A sample of 128 parents in Germany with preschool children (aged 2 to 6 years) participated in an online survey. The survey assessed three key periods: before the nationwide lockdowns (retrospectively), during the most challenging phase of the lockdown (retrospectively), and after the lockdowns were lifted. Symptoms of depression and anxiety were investigated with validated questionnaires and pandemic-specific stressors (e.g., isolation of child) with a self-developed set of 23 items. Descriptive statistics, group comparisons, and hierarchical multiple regression analyses were conducted. Results Symptoms of anxiety and depression significantly increased during lockdowns in comparison to before pandemic onset and remained elevated after restrictions eased. Key predictors of poorer mental health included pre-pandemic symptoms, lower parental education, concerns about access to primary care, and children's social isolation during lockdowns. Demographic factors alone were not consistently significant predictors. Conclusions Symptoms of anxiety and depression significantly increased during lockdowns compared to before pandemic onset and remained elevated after restrictions eased. COVID-19-related stressors played a greater role in parental mental health outcomes than demographic variables. These findings emphasize the need for early identification of at-risk families and the development of targeted interventions to support parental well-being in future public health emergencies.